Respuesta :
(1.6 * 10^3) * (3.0 * 10^-6) =
(1.6 * 3.0) * (10^3 * 10^-6)
4.8 * 10^(3 - 6) =
4.8 * 10^-3 =
4.8 * 1/10^3 =
4.8 / 10^3 =
4.8 / 1000 =
0.0048 <==
(1.6 * 3.0) * (10^3 * 10^-6)
4.8 * 10^(3 - 6) =
4.8 * 10^-3 =
4.8 * 1/10^3 =
4.8 / 10^3 =
4.8 / 1000 =
0.0048 <==
Answer:
[tex]1.6\cdot 10^3\times 3.0\cdot 10^{-6}=4.8\times10^{-3}[/tex]
Step-by-step explanation:
Given : Expression [tex]1.6\cdot 10^3\times 3.0\cdot 10^{-6}[/tex]
To find : Calculate the given expression?
Solution :
Step 1 - Write the expression
[tex]=1.6\cdot 10^3\times 3.0\cdot 10^{-6}[/tex]
Step 2 - Taking 10 power together
[tex]=(1.6\times 3)\times(10^3\times 10^{-6})[/tex]
Step 3 - Solve the multiplication and if base are same then in multiplication power get added.
[tex]=4.8\times10^{3-6}[/tex]
[tex]=4.8\times10^{-3}[/tex]
Therefore, The solution of expression is
[tex]1.6\cdot 10^3\times 3.0\cdot 10^{-6}=4.8\times10^{-3}[/tex]